The risk of hepatitis B virus reactivation and the role of antiviral prophylaxis in hepatitis B surface antigen negative/hepatitis B core antibody positive patients with diffuse large B-cell lymphoma receiving rituximab-based chemotherapy. Issue 4 (April 2015) - Lu, Shasha; Xu, Yu; Mu, Qitian; Cao, Lihong; Chen, Jian; Zhu, Zhijuan; Lou, Yinjun; Meng, Haitao; Qian, Wenbin; Tong, Hongyan; Mai, Wenyuan; Huang, Jian; et al.
Abstract The risk factors and the role of prophylactic antiviral therapy of hepatitis B virus (HBV) reactivation in patients with hepatitis B surface antigen (HBsAg) negative/hepatitis B core antibody (HBcAb) positive disease remain controversial. We reviewed 629 patients with diffuse large B-cell lymphoma (DLBCL). Among 629 patients, 150 of 246 patients with resolved HBV (HBsAg negative and HBcAb positive) were treated with rituximab-combined therapy. Among these 150 patients, none of 104 patients (0.0%) who were hepatitis B surface antibody (HBsAb) positive experienced HBV reactivation versus four of 46 patients (8.7%) who were HBsAb negative (p = 0.008). One of 113 patients (0.9%) with International Prognostic Index (IPI) 0–2 suffered HBV reactivation versus three of the remaining 37 patients (8.1%) with IPI 3–5 (p = 0.047). HBsAb and IPI are potential risk factors for HBV reactivation. The use of prophylactic agents may not be recommended for these patients until the occurrence of HBV reactivation.